Digital Storytelling With Youth From Refugee Backgrounds: Possibilities for Language and Digital Literacy Learning. Issue 3 (22nd April 2022) - Kendrick, Maureen; Early, Margaret; Michalovich, Amir; Mangat, Meena
Abstract: This study addresses the urgent need to develop innovative pedagogies that build upon and enhance the digital literacies and representational practices of culturally and linguistically diverse youth from refugee backgrounds. In Canadian high schools, this population of students enter school with varying levels of literacy in their first language(s), as well as potentially difficult experiences due to their forced migration. For many, learning English, may become a formidable challenge. A growing corpus of case studies is beginning to show how pedagogies that draw on youths' everyday meaning making, including their digital literacies, can effectively engage English learners in academic learning. In this qualitative, ethnographic case study involving nine youth in an English language learning classroom, we addressed the question: What is the potential for digital storytelling to draw from the fuller context of the lives and literacies of youth from refugee backgrounds to enable more autonomous language learning and identity affirmation? Our study is informed by interrelated conceptual frameworks: learner autonomy; investment in language and literacy learning; and digital literacies. Using thematic and multimodal/visual analysis, data were collaboratively coded to identify four interweaving themes: 1) use of multimodal meaning making to communicate complex, critical understandings; 2) emergence of digital literacies; 3) challenges of communicating in digital spaces; and 4) investment in identity affirmation in language learning. Implications focus on how digital storytelling as an innovative pedagogy has the potential to create space within the curriculum for stories that have deep meaning for learners.